ANALISIS KEPATUHAN WAJIB PAJAK BERDASARKAN REALISASI PENERIMAAN PBB PADA BPPKAD KABUPATEN PURWOREJO - Inge Hasna Puspita; Supanji Setyawan (Transpublika Publisher, 2022)
Land and Building Tax (PBB) is a Regional Tax as one of the key sources of regional income to pay local government administration in order to establish a realistic and accountable regional autonomy. Therefore, tax payer compliance in meeting their tax collection obligations is required. The achievement of revenue targets and Building Tax (PBB) demonstrates tax compliance. This research was conducted in the BPPKAD Purworejo Regency. In this study, the author investigates the Taxpayer Compliance Analysis Based on PBB Revenue. The aim of this research is to determine what proportion of PBB tax income is collected depending on tax compliance (PBB). This study employs descriptive method, and data is collected from BPPKAD Purworejo Regency and processed by examining the proportion of realized land and building tax collections (PBB). The result reveal that the number of Land and Building Tax payers increases annually from 2016 to 2019. The rise in the number of tax payers means that the potential for PBB revenue will increase every year. For the realization of PBB revenue level Land Tax payer compliance and buildings (PBB) of Purworejo Regency, namely paying taxes as considered necessary.